A Model of Small Capacity Power Plant in Tateli Village, North Sulawesi. (March 2017) - Sangari, F J; Rompas, P T D
Abstract: The electricity supply in North Sulawesi is still very limited so ubiquitous electric current outage. It makes rural communities have problems in life because most uses electrical energy. One of the solutions is a model of power plants to supply electricity in Tateli village, Minahasa, North Sulawesi, Indonesia. The objective of this research is to get the model that generate electrical energy for household needs through power plant that using a model of Picohydro with cross flow turbine in Tateli village. The method used the study of literature, survey the construction site of the power plant and the characteristics of the location being a place of research, analysis of hydropower ability and analyzing costs of power plant. The result showed that the design model of cross flow turbines used in pico-hydro hydropower installations is connected to a generator to produce electrical energy maximum of 3.29 kW for household needs. This analyze will be propose to local government of Minahasa, North Sulawesi, Indonesia to be followed.